2011
DOI: 10.1002/bsl.1009
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal examination of sex offender recidivism prior to and following the implementation of SORN

Abstract: The goals of the present study were to examine the recidivism rates of two matched samples of sexual offenders, those released prior to and after sex offender registration and notification (SORN) in New Jersey. The pre-SORN group (1990-1994) included 247 offenders, while the post-SORN group (1996-2000) included 248 offenders. The longitudinal analysis demonstrated that for sex offenders released from prison both prior to and after implementation of SORN, there are clearly two distinguishable groups of sex offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 62 publications
0
63
1
1
Order By: Relevance
“…Other studies, which followed participants from youth through adulthood (Andersson et al, 2012;Bersani et al, 2009;D'Unger et al, 1998D'Unger et al, , 2002Eggleston et al, 2004;Huesmann et al, 2009;Jones et al, 2001;Kreuter & Muthén, 2008;Laub et al, 1998;Nagin et al, 1995;Piquero, Farrington, et al, 2010;Sampson & Laub, 2003) had at least one, and in many cases more than one, group of life-course persistent offenders. Teacher-rated disruptive behaviors SAS 820 girls from Quebec followed for 10 years (1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996) 4 Low (57.4%) Medium (31.6%) Medium-High (9.6%) High (1.4%) Coté et al, 2002aCoté et al, , 2002b Teacher-rated impulsivity SAS 1,865 boys and girls in Quebec followed from kindergarten through grade six Freiburger et al, 2012;Tewksbury & Jennings, 2010;Tewksbury et al, 2012; Homicide perpetrators only: Vaughn et al, 2009;Burglars only: Vaughn et al, 2008;Drug users only: Vaughn et al, 2012;African Americans only: Higgins, Bush, et al, 2010;Higgins et al, 2012;Hispanics only: Maldonado-Molina et al, 2009;Maldonado-Molina, Reingle, et al, 2010;Reingle et al, 2011;Parochial school students: Lynne-Landsman et al, 2011);and geographical location (Andersson et al, 2012;Bersani et al, 2009;…”
Section: Shape Of Trajectoriesmentioning
confidence: 99%
“…Other studies, which followed participants from youth through adulthood (Andersson et al, 2012;Bersani et al, 2009;D'Unger et al, 1998D'Unger et al, , 2002Eggleston et al, 2004;Huesmann et al, 2009;Jones et al, 2001;Kreuter & Muthén, 2008;Laub et al, 1998;Nagin et al, 1995;Piquero, Farrington, et al, 2010;Sampson & Laub, 2003) had at least one, and in many cases more than one, group of life-course persistent offenders. Teacher-rated disruptive behaviors SAS 820 girls from Quebec followed for 10 years (1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996) 4 Low (57.4%) Medium (31.6%) Medium-High (9.6%) High (1.4%) Coté et al, 2002aCoté et al, , 2002b Teacher-rated impulsivity SAS 1,865 boys and girls in Quebec followed from kindergarten through grade six Freiburger et al, 2012;Tewksbury & Jennings, 2010;Tewksbury et al, 2012; Homicide perpetrators only: Vaughn et al, 2009;Burglars only: Vaughn et al, 2008;Drug users only: Vaughn et al, 2012;African Americans only: Higgins, Bush, et al, 2010;Higgins et al, 2012;Hispanics only: Maldonado-Molina et al, 2009;Maldonado-Molina, Reingle, et al, 2010;Reingle et al, 2011;Parochial school students: Lynne-Landsman et al, 2011);and geographical location (Andersson et al, 2012;Bersani et al, 2009;…”
Section: Shape Of Trajectoriesmentioning
confidence: 99%
“…In a study in Iowa, Tewksbury and Jennings (2010) examined the three distinct post-release trajectories of reconviction for a pre-SORN and a post-SORN group, and found them to be of similar shape with similar proportions of offenders; there was no statistical evidence of any effect of the SORN legislation. Similarly, a study in New Jersey (Tewksbury et al, 2012) found no differences in either the shape or proportions of offenders in the two trajectory groups.…”
Section: Sex Offender Registration and Notification Schemesmentioning
confidence: 92%
“…Since inception, the effectiveness of SORN and residence restrictions have been the subject of extensive debate and criticism. Empirical findings reveal sex offender management policies have little to no effect on sex offender recidivism (Letourneau, Levenson, Bandyopadhyay, Sinha, & Armstrong, 2010;Tewksbury, Jennings, & Zgoba, 2012). Additionally, several scholars reveal several unintended consequences stemming from these policies, chief among them being loss of housing, difficulty finding employment, social isolation, emotional suffering, and harassment by other community members (Levenson & Cotter, 2005a, 2005bLevenson & Hern, 2007;Tewksbury, 2005;Tewksbury & Mustaine, 2009).…”
Section: Introductionmentioning
confidence: 92%